Determinants of Exporter’s Intention in Using Sharia Letter of Credit Products - Siti Fatimah Azzahro; Irham Amir (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
This study aims to determine the factors that influence the intention of exporters to use a Sharia Letter of Credit. This study uses four variables, namely Islamic financial literacy, sharia-compliant perception, technology factors, and financing facilities. This research uses Partial Least Square Structural equation modeling (SEM) approach was used to test the measurement model (outer model) and structural model (inner model). The purpose of the two stages of evaluation of the measurement model is to assess the validity and reliability of a mode. Online questionnaires were distributed to purposively selected respondents throughout Indonesia. The respondents are 80 decision-makers in export companies and people who have export-worthy products in Indonesia. This study found that the variables of Islamic financial literacy, technology factors, and financing facilities as independent variables significantly influence the intention to use a sharia letter of credit. Meanwhile, the variable of sharia-compliant perception was not proven to have a significant effect.